El castigo silencioso de los detenidos en prisión preventiva - Lages, Lívia Bastos; Ribeiro, Ludmilia Mendonça Lopes (El Colegio de México, 2021)
Abstract: This article seeks to understand the decision-making behind custody hearings, which determine whether a person caught red-handed should be held in remand or released. Using data from 380 custody hearing decisions in Belo Horizonte (Minas Gerais, Brazil), binomial logistic regression models were used to calculate the likelihood of remand. The results show that the severity of the criminal offense as well as the suspect’s criminal career significantly influence the pre-trial detention outcome. Results are similar to those of other research undertaken in Latin America.